Peningkatan pengetahuan dan ketrampilan menyediakan makanan sehat dan hand sanitizer alami dalam menghadapi pandemic Covid19 - Happy Elda Murdiana; Nikasius Jonet Sinangjoyo; Sarah Puspita Atmaja; Lea Oktavining Tyas (Institut Teknologi Dirgantara Adisutjipto, 2021)
The covid 19 pandemic has not ended and there are still many people who have not received the vaccine scheduled by the government so all citizens must remain vigilant against Corona 19 virus infection. Viral infection is a self-limiting disease that can heal itself if our immune system is strong. There are many things that can increase the immune system, one of which is nutritional intake from food and proper processing methods. Fulfillment of macro nutrition in the form of energy and protein sources can be obtained from animal and vegetable sources, while micronutrients in the form of vitamins and minerals can be obtained from meat, fish, vegetables, colored fruit or not. The content of micronutrients that increase immunity is in the form of antioxidants contained in vitamins A, B, C, E, zinc, Fe and several other minerals. Washing hands with soap or hand sanitizer is a government program to prevent the spread of the covid 19. The high cost of hand sanitizers and the scarcity of goods have led to creative ideas to empower people in making hand sanitizers that are cheap, easy to obtain and safe for all ages. The aim of this community service is to provide understanding to the community about sources of nutrition to increase the body's immune system and how to properly process food ingredients without damaging nutritional content and improve skills in processing food ingredients and making hand sanitizers from environmentally friendly natural ingredients that can be taken from around us. Community service can be carried out well, the community feels very helped by the counseling and training provided. Evaluation of activities is carried out by assisting the community's creativity in processing nutritious food and making hand sanitizers with natural ingredients around our environment.